The effects of lexical frequency and homophone neighborhood density on incomplete tonal neutralization - Bi, Yifei; Chen, Yiya (Frontiers in Psychology, 2022)
We investigated the effects of lexical frequency and homophone neighborhood density on the acoustic realization of two neutralizing falling tones in Dalian Mandarin Chinese. Monosyllabic morphemes containing the target tones (Tone 1 and Tone 4) were produced by 60 native participants from two generations (middle-aged vs. young). The duration of tone-bearing syllable rhymes, the lexical tone F0 curves, and velocity profiles were quantitatively analyzed via linear mixed-effects modeling and functional data analysis. Results showed no durational difference between T1 and T4. However, the F0 contours of the two falling tones were incompletely neutralized for both young and middle-aged speakers. Furthermore, the degree of T1-T4 F0 neutralization varied as a function of the lexical property of the tone-carrying syllables. Lexical frequency showed little effect on incomplete tonal neutralization. There were significant differences in the turning point of the two falling tones in syllables with both high and low lexical frequency. Homophone neighborhood density showed an effect on the incomplete neutralization between the two falling tones, reflected in significant differences in the slope and turning point of the F0 velocity profiles between the two tones carried by syllables with low density but not high density. Moreover, homophone neighborhood density also affected the duration, the turning point of F0 curves, and velocity profiles for the T1- and T4-syllables, respectively. These results are discussed with consideration of social variations, the Hypo- and Hyper-articulation (H&H), the Neighborhood Activation Model, and the information-based model. Conjointly, these results extend our understanding of the effects of lexical properties on the acoustic details of lexical tone production and tonal sound changes.